2007
DOI: 10.1007/s00018-007-6513-4
|View full text |Cite
|
Sign up to set email alerts
|

RNA and protein-dependent mechanisms in tauopathies: consequences for therapeutic strategies

Abstract: Tauopathies are a group of neurodegenerative diseases characterised by intracellular deposits of the microtubule-associated protein tau. The most typical example of a tauopathy is Alzheimer's disease. The importance of tau in neuronal dysfunction and degeneration has been demonstrated by the discovery of dominant mutations in the MAPT gene, encoding tau, in some rare dementias. Recent developments have shed light on the significance of tau phosphorylation and aggregation in pathogenesis. Furthermore, emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 141 publications
(176 reference statements)
1
21
0
Order By: Relevance
“…A mutation that falls into a silencer or enhancer regions either promotes or decreases exon usage, respectively (reviewed in [80]). Mutations in exon 10 alter its normal fraction of inclusion and changes of pre-mRNA encoding 3R and 4R repeat tau isoforms were found associated with FTDP-17 (recently reviewed by [81], [82]). These data clearly suggested that the splicing mutations cause the neuropathology by changing the ratio between the 3R and 4R isoforms.…”
Section: Examples Of Diseases Caused By Alternative Splicingmentioning
confidence: 99%
“…A mutation that falls into a silencer or enhancer regions either promotes or decreases exon usage, respectively (reviewed in [80]). Mutations in exon 10 alter its normal fraction of inclusion and changes of pre-mRNA encoding 3R and 4R repeat tau isoforms were found associated with FTDP-17 (recently reviewed by [81], [82]). These data clearly suggested that the splicing mutations cause the neuropathology by changing the ratio between the 3R and 4R isoforms.…”
Section: Examples Of Diseases Caused By Alternative Splicingmentioning
confidence: 99%
“…To increase specificities, multiple technologies to target aberrant splicing (Gallo et al, 2007) have been examined for SMN genes. One strategy that is employed to stimulate inclusion or exclusion of exon 7 is to use bifunctional oligoribonucleotides, which are molecules made of an anti-sense sequence that bind to an exonic element and a sequence tethering a trans factor, or link to a peptide domain mimicking a trans splicing factor (Cartegni and Krainer, 2003;Skordis et al, 2003;Villemaire et al, 2003).…”
Section: Sma Animal Modelsmentioning
confidence: 99%
“…The abnormal hyperphosphorylation and altered conformation of the microtubule-associated protein (MAP) tau precedes its assembly into paired helical filaments and its accumulation in NFTs (Buee et al, 2000; Andorfer et al, 2003; Gallo et al, 2007; Hanger et al, 2009; Iqbal et al, 2009). Tau is a substrate for several protein kinases, such as glycogen synthase kinase-3 (GSK-3) and cyclin-dependent kinase (cdk5), and for phosphatases such as protein phosphatase-2A (PP2A); PP2A activity is down-regulated in the AD brain (Buee et al, 2000; Andorfer et al, 2003; Gallo et al, 2007; Hernandez and Avila, 2008; Hanger et al, 2009; Iqbal et al, 2009; Hernández et al, 2010).…”
Section: Is There a Link Between At2r Activation And Ad?mentioning
confidence: 99%